Influence of operational parameters and kinetics analysis on photocatalytic hydrolysis of ammonia borane for H2 production used heterojunction FeTiO3/TiO2-decorated carbon nanofibers - Abdullah M. Al-Enizi; Ayman Yousef; Mohd Ubaidullah; Alamgir Karim; M.M. El-Halwany (Journal of King Saud University: Science, 2023)
In this work, carbon nanofibers (CNFs) decorated with heterojunction iron titanate/titanate nanoparticles (FeTiO3/TiO2 NPs) were effectively prepared using electrospinning for use as a photocatalyst in the production of hydrogen (H2) from ammonia borane (AB). The as-prepared FeTiO3/TiO2@CNFs exhibited strong photocatalytic activity for H2 release from photohydrolysis of the AB when exposed to visible light. Under visible light illumination, the observed H2 evolution over TiO2@CNFs was 0.38 mol in 14 min, whereas over FeTiO3/TiO2@CNFs it was 2.97 mol. Using FeTiO3/TiO2@CNFs, H2 generation was shown to be substantially higher under visible light irradiation (2.97 mol/14 min) than in the dark (1.87 mol/14 min). A mathematical model was used to predict the photocatalytic activity of FeTiO3/TiO2@CNFs. Different operational factors were used to verify the accuracy of the mathematical model; they included the impact of AB concentration, light intensity, reaction temperature, and catalyst dosage. The reaction rate constant and equilibrium concentration were measured experimentally and compared to those predicted by the model. A good correlation was obtained between the calculated and measured photocatalytic activity.